Silkeborgkontorets sidste dage. Peder Herschends dagbog omkring den tyske kapitulation maj 1945 - Lauridsen, John T. (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2014)
NB: Artiklen er på dansk, kun resuméet er på engelsk. In November 1943, the German Wehrmacht’s Commander-in-Chief in Denmark, Hermann von Hanneken, moved his headquarters from Copenhagen to Silkeborg. He demanded that a representative of Danish department heads be sent there to ensure efficient arrangement for, and implementation of, the Wehrmacht’s needs. The department heads unanimously appointed Chief County Administrator Peder Herschend to “provisionally carry out the central administration and administer its central institutions according to due process of law on their behalf for urgent decisions.” Herschend took on the task and established an office in Silkeborg (the Silkeborg Office) to this end. He was assisted by a small, experienced staff of civil servants, some of them from the Ministry of Foreign Affairs. Until May 1945, Herschend functioned as adviser to the Danish authorities in Jutland and on Funen and as intermediary with the German headquarters when necessary. The Silkeborg Office was closed on 16 May. An official log was kept at the Silkeborg Office from November 1943 to May 1945. Notes were kept on all the cases with which the Office had to deal. The log is in five volumes, consisting of a total of approximately 7,000 pages, in which some 3,036 cases were recorded. There is one copy of the log in the National Archives and one at the Royal Library (Herschend’s copy). The National Archive’s copy contains only the log cases while the Royal Library’s copy also has a volume with the telegrams exchanged between Herschend and the Ministry of Foreign Affairs. The log has by no means been ignored but has been used only rarely. It is a unique source of information on many aspects of German occupation policy in Denmark at the regional level, particularly indispensable given that nearly all of the corresponding German archives were destroyed. The log covering the period from 4 May to 16 May 1945 has now been published in its entirety. It bears witness not only to a role change during the days of capitulation in which it was no longer the occupying power that decreed and confiscated but also to the fact that liberation brought many new problems and other players onto the scene. The Silkeborg Office handled everything professionally. If there was a celebratory atmosphere in the Office on 4 and 5 May, this was not commented on in the log. Herschend and his co-workers sought throughout the entire process to maintain an official style that, in numerous cases, was the only means of satisfying the Germans.